Repercusión en el derecho a la vida en Perú en la jurisprudencia constitucional y resolución del ministerio de salud respecto a la píldora del día siguiente - Toribio Juárez, Alicia (2011)
To have been issued in Peru two resolutions whose contents are conflicting as to the constitutional right to life, a Resolution N° just about this issue -SA/DM issued by the Ministry of Health and the Resolution N° 02005-2009-PA/CT scan of the Constitutional Court of Peru was of interest to explore the impact both in the legal field as well as a social. To demonstrate this, it then proceeded to take information on those resolutions, which have formed the material for the study, for which he was useful the analytic-synthetic method to identify the contradictory aspects of these two legal instruments aimed at the right to life of the unborn child. The data is presented in a comparative table, which highlights the approval of the Ministry of Health to distribute the pill emergency oral and the judgment of the Constitutional Court, in the which prohibits its free distribution. It is implicit in respective analysis that both resolutions affect the Peruvian legal system, on the one hand it allows for the use and on the other hand is prohibited by its free distribution without express an opinion on the merits, to indicate what is abortion pill, in this way the right of the unborn child passes to a plane intermediated by the market and the duality.